Vocational Education in Indonesia Facing ASEAN Economic Community - KASIM YAHIJI; CHOIRUL MAHFUD; MUHAMMAD ARFAN MU'AMMAR (Universitas Jambi, Indonesia, 2019)
Nowadays, vocational education and the ASEAN Economic Community (AEC) are an interesting topic to discuss for contributing to the ASEAN future. This article explores the vocational education in Indonesia facing ASEAN Economic Community. Vocational education is clearly significant not only to help the government but also to determine the future direction of the people and the nation. This article describes the condition of vocational education in facing ASEAN Economic Community. Also, this article explores the strategic roles in the development of vocational education in the ASEAN Economic Community (AEC) era for the benefit of the nation which is expected by all, especially for society, nation, and the world through reviewing references and literature books, news, journals and opinions in mass media and various related publications and sources. The article discusses the contributions from all stakeholders of education from civil society organizations in Indonesia that are very significant for facing AEC. Implications for educational policies on vocational education are also presented.